Chemical composition optimization of nanocomposites used for shed and core of outdoor composite insulators - Gafti, Abdolah; Taherian, Reza; Kiahoseini, Seyed Rahim (Frontiers in Materials, 2022)
Outdoor 24-kV power transmission insulators include two main pieces, namely, the shed and core. In this study, these pieces were manufactured separately by roll/hot pressing and hand lay-up methods, respectively. Both shed and core were formed from polymer-based composites due to their low weight, high strength-to-weight ratio, and higher moisture and pollution resistance compared to those of ceramic and glass sheds. The sheds were made from silicone rubber as the matrix and alumina trihydrate (ATH) and TiO2 as additives in single- and double-filler composites. The characterization tests of the sheds included variable (max stability voltage) and constant (dry, wet, and notched max endurance voltage, as well as erosion) voltage tests, in addition to contact angle tests. The results of these analyses demonstrated that silicone rubber reinforced with 5 wt.% TiO2 was the best shed material based on its hydrophobicity. The core of the insulator was made of epoxy reinforced with different glass fiber percentages (10, 13, and 15 wt.%). The manufacturing method was hand lay-up. Tensile strength and scanning electron microscopy (SEM) were used for characterization.